Faktor - faktor yang Memengaruhi Kinerja Guru Yayasan Marsudirini Kota Semarang Tahun Pelajaran 2021-2022 - V.Naniek Risnawati; Anastasia Lipursari; Marius Pramana (Jurnal Administrasi dan Kesekretarisan, 2022)
Factors Affecting the Teachers’ Performance at Yayasan Marsudirini Semarang. The study aims to find out how much factors affecting the performance of the teachers at Yayasan Marsudirini in Semarang. Data was collected through observation, and as many as 101 teacher questionnaires were used to assess pedagogic, professional and personality competencies of the teachers Data was analyzed using descriptive qualitative with percentage technique. The results showed that the factors influencing the performance of the teachers of Yayasan Marsudirini Semarang in this study were the principal's managerial and teachers’ loyalty. The results of this study are 1) the principal’s managerial supports institutional activities in which more than 50% of teachers with the principal’s activities "always" support the institution starting from planning, creating vision and mission guided by evaluation, coordinating in decision making, regularly holding meetings for teacher councils, supervising teachers and employees, improving teacher performance, improving the quality of education, motivating teachers in the learning process, communicating with teachers and employees in overcoming problems, and naturally social in giving services. 2) teachers’ loyalty in learning includes: cognitive, affective and psychomotor aspects in accordance with the supervision of the principal, the results obtained are more than 50% of teacher activities marked "always" which means that teacher carries out obligations in accordance with applicable rules in schools and foundations (yayasan), they obey the teacher's code of ethics, discipline, and being faithful in providing services, and to give guidance to students in the study and development of the student personality. In addition, teachers have creativity skill and high motivation for personal development, school and community. Penelitian ini memiliki tujuan untuk mengetahui beberapa faktor yang memengaruhi kinerja guru Yayasan Marsudirini di Kota Semarang. Metode pengumpulan data yang dipakai adalah angket dan observasi. Angket dibagikan kepada 101 guru. Untuk menilai kompetensi pedagogik, profesional dan kepribadian. Analisis data menggunakan deskriptif kualitatif dengan teknik prosentase. Hasil penelitian menunjukkan bahwa faktor yang memengaruhi kinerja guru Yayasan Marsudirini kota Semarang dalam penelitian ini adalah manajerial kepala sekolah dan loyalitas guru. Adapun hasil yang diperoleh 1) Manajerial Kepala Sekolah : selalu mendukung kegiatan lembaga diperoleh lebih dari 50% guru dengan kegiatan - kegiatan kepala sekolah mulai perencanaan penyusunan visi misi sekolah yang berpedoman pada evaluasi, selalu melakukan koordinasi dalam pengambilan keputusan, secara rutin mengadakan rapat dewan guru, melakukan pengawasan kepada guru dan karyawan, meningkatkan kinerja (Restatilahm Fenti et al., 2020) guru,meningkatkan mutu pendidikan memotivasi guru dalam proses pembelajaran, berkomunikasi dengan guru dan karyawan dalam mengatasi permasalahan, bersifat sosial (kekeluargaan).2) loyalitas kerja guru dalam pembelajaran meliputi : aspek kognitif, afektif dan psikomotorik sesuai dengan pengawasan kepala sekolah diperoleh hasil lebih dari 50% kegiatan guru “Selalu” artinya dalam melaksanakan kewajiban sesuai dengan aturan yang berlaku, mentaati kode etik guru, disiplin, serta setia dalam memberikan pelayanan, bimbingan kepada para siswa dalam studi maupun pengembangan kepribadian siswa. Dan mempunyai daya kreativitas serta motivasi yang tinggi untuk pengembangan pribadi, sekolah maupun masyarakat.